Analisis Pengembangan Soal Berbasis HOTS (Higher Order Thinking Skills) Mata Kuliah Belajar dan Pembelajaran FTK UIN Mataram - Annisa Aprilia; Sibawaihi Sibawaihi; Akhmad Asyari (ISLAMIKA, 2023)
This research is based on the demands of students to be able to improve their critical thinking skills in the era of industrial disruption. So this study aims to analyze the characteristics of HOTS-based question development and analyze the steps of lecturers in the preparation of HOTS-based questions in learning and learning courses at FTK UIN Mataram. . By type, it belongs to the category of field research in a qualitative approach. The authors collect data by interviewing and documenting. From the results of the study, it was found that the characteristics of the questions developed include the appropriate cognitive level, namely analyzing, evaluating and creating, as well as using stimulus and response. Then the steps taken by lecturers in the study and learning courses to develop HOTS questions have met the standard procedure for making questions. A series of stages in the procedure for compiling HOTS questions that have been made by lecturers studying and learning FTK UIN Mataram are:: 1) Analyze basic competencies as basic HOTS questions. 2) Designing the Question grid. 3) Presenting interesting but contextual stumulus., finally 4) Compiling questions based on a grid that has been arranged.